EMERGENCE OF ECOLOGY AS A KEYSTONE DISCIPLINE FOR THE SURVIVAL OF MAN AND BIOSPHERE - A LOOK FOR A LOGIC - Datta, N C (Journal of the Inland Fisheries Society of India, 2016)
EMERGENCE OF ECOLOGY AS A KEYSTONE DISCIPLINE FOR THE SURVIVAL OF MAN AND BIOSPHERE - A LOOK FOR A LOGIC